Secret Relationships and Clandestine Encounters: an Ethnography of Youth Romance and Marriage among Javanese Male Sex Workers in South Bali (Indonesia) - Alcano, Matteo Carlo (Richtmann Publishing, 2012)
This article is intended as an ethnographic and theoretical reflection on the significance of courtship practices and marriageamong lower classes Indonesian youth. It also discusses gender roles and social transformation. It is based on fieldwork researchcarried out in Bali and East Java between 2008 and 2010 among a gang of male sex workers. The article discusses the importance ofsecret relationships and clandestine encounters, pacaran backstreet, between Javanese male sex-workers who cater the homosexualsex market and migrant female workers in Bali, and the role of marriage as a cognitive resource in the transition to adulthood in thecontext of sex work. It sheds light on alternative forms of masculine identity and on articulations of juvenile malaise, gang affiliation,corporeal practices, male bonds of solidarity, reciprocity and respect, and their impact on the construction of interpersonal emotionalrelations. It draws conclusions about the role of customary practices and values in the lives of young men (and women) in a specificsector of contemporary Indonesian society.